Evaluasi Struktur dan Skala Upah (SSU) Menggunakan Metode Overlapping pada UKM Mphoto Studio Bekasi - Farah Anindya; Feyza Tiftazani; Yolanda Salsabila; Donita Fahdini Amalina; Ladysa Saskia Siahaan; Nurul Hidayati (BADAN PENERBIT STIEPARI PRESS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia’s economic growth but often face challenges in managing human resources, particularly in implementing fair and efficient compensation systems. This study was conducted at Mphoto Studio, an MSME in Bekasi, to evaluate the wage structure and salary scale of employees, and to analyze the effectiveness of the overlapping method in creating a more proportional and sustainable compensation system. This study applied both qualitative and quantitative methods through interviews and salary mapping analysis conducted between April and June 2025. The findings revealed that the existing wage structure prior to adjustment did not reflect principles of fairness, with most employees earning below the Bekasi city minimum wage. After applying the overlapping method, the salary structure became more systematic, flexible, and aligned with job grades. Despite a 6.6% increase in total salary expenses, the new structure remained within the company’s budget capacity. This study concludes that the overlapping method is an effective and feasible approach for designing compensation structures within MSMEs.